Disaster Literacy based on local wisdom to instill Disaster Response in Selo, Boyolali Regency - Mukhlis Mustofa; Goddess Liesnoor Setyowati; Juhadi; Suwito eco Pramono (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
The planting of early disaster education in the Merapi area is a must in the midst of the great potential for disaster in it. This awareness planting can be strengthened by literacybased learning by paying attention to the local wisdom adopted by the people who live in it. This study aims to determine the understanding of elementary school teachers about disaster literacy in social studies learning associated with understanding local wisdom in preparing learning and disaster response attitudes on the slopes of Merapi. This study uses a descriptive qualitative research approach by taking the location at SD Jrakah 3 Selo , Boyolali Regency. Based on the results of the research that has been carried out, it can be concluded as follows: 1) Social studies learning by planting disaster literacy based on social studies teaching materials and local wisdom has not fully used the latest learning media in improving students' skills for developing disaster response attitudes. 2) Teacher understanding and interest in disaster literacy and understanding local wisdom in the development of disaster education affects the growth of disaster response for students